Analisis Yuridis Majelis Kehormatan Notaris Wilayah Riau Sebagai Tergugat dalam Pemberian Persetujuan Pemanggilan Notaris oleh Penyidik: Studi Putusan Mahkamah Agung No. 36 PK/TUN/2020 - Tri Andhika; Sutiarnoto; suprayitno (Himpunan Ilmu Hukum dan Ilmu Hukum Islam, 2026)
The Regional Notary Honor Council (MKNW) holds attributive authority under Article 66 paragraph (1) of Law No. 2 of 2014 in granting approval for the summoning of a notary as a witness in criminal law enforcement. Using a normative descriptive-analytical method, the findings indicate that the MKNW is obliged to act actively and selectively through a plenary session based on verified facts. The MKNW of Riau is legitimately established as a State Administrative Body, as its approval letter fulfills all elements of a State Administrative Decree that is concrete, individual, and final. The Supreme Court in Decision No. 36 PK/TUN/2020 affirmed that non-essential procedural deficiencies cannot invalidate the legitimacy of the decision as long as the substantive rights of the notary to be heard remain fulfilled.